Agenda Pemilu Serentak: Pemisahan Pemilu Nasional dan Pemilu Lokal [Concurrent Elections: Separating the National and Local Elections - Prayudi Prayudi (Sekretariat Jenderal DPR RI, 2021)
The concurrent elections became one of the agendas in the preliminary revised draft of the General Elections Bill by the Indonesian House of Representatives following Decision of Constitutional Court Number: 55/PUU-XVII/2019. One of the agendas proposed in revised bill was the separation between the national and local elections. The article uses the theory of embedded democracy to further identify several factors that underlie the importance of separating national and local elections in the concurrent election agenda. The relevant factors that come into play include political patterns of power and public participation, political party dynamics, the foundation of government superstructure, national-local government relations, as well as the advantages and drawbacks of voters’ personal sentiments. The substance of embedded democracy theory, as shown by the aforementioned factors, suggests that separation between national and local elections should be considered in the organization of the concurrent elections in Indonesia after the upcoming 2024 elections.AbstrakAgenda pemilu serentak menjadi salah satu muatan dari draft rancangan revisi UU Pemilu yang dilakukan oleh DPR setelah keluarnya Putusan MK No. 55/PUU-XVII/2019. Salah satu muatan agenda tadi adalah gagasan yang mencoba untuk memisahkan pemilu nasional dan pemilu lokal. Tulisan ini menggunakan teori demokrasi yang tertanam guna mengidentifikasi lebih lanjut beberapa faktor yang mendasari pentingnya pemisahan pemilu nasional dan pemilu lokal dalam agenda pemilu serentak. Beberapa faktor dimaksud yaitu pola politik kekuasaan dan partisipasi masyarakat, kehidupan partai politik, landasan suprastruktur pemerintahan, dan hubungan pusat-daerah, serta peluang dan tantangan sentimen pemilih itu sendiri. Substansi demokrasi tertanam teoritik sebagaimana ditunjukkan oleh faktor-faktor tersebut menunjukkan bahwa skema pemilu nasional dan pemilu lokal yang dipisah, kiranya penting dipertimbangkan bagi penyelenggaraan agenda pemilu serentak di Indonesia sesudah Pemilu 2024 mendatang.